If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 38x + 1 = 9(4x + -7) Reorder the terms: 1 + 38x = 9(4x + -7) Reorder the terms: 1 + 38x = 9(-7 + 4x) 1 + 38x = (-7 * 9 + 4x * 9) 1 + 38x = (-63 + 36x) Solving 1 + 38x = -63 + 36x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36x' to each side of the equation. 1 + 38x + -36x = -63 + 36x + -36x Combine like terms: 38x + -36x = 2x 1 + 2x = -63 + 36x + -36x Combine like terms: 36x + -36x = 0 1 + 2x = -63 + 0 1 + 2x = -63 Add '-1' to each side of the equation. 1 + -1 + 2x = -63 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = -63 + -1 2x = -63 + -1 Combine like terms: -63 + -1 = -64 2x = -64 Divide each side by '2'. x = -32 Simplifying x = -32
| 3(x+8)-7=0 | | 5y^4=-2y+3 | | (8a^-6b^2/11a^4b^-9)^0 | | 4/3b-1/6=5/6b | | x^2+50x=-5000 | | [8a^-6b^2/11a^4b-9]^0 | | fx=x^2+50x+5000 | | -6x-7y=3 | | 1n/6=11/3 | | 19-0.7y=1.5y+8 | | 0.25k-14=-3.75k | | 5-4x+6=3x+(7-4x) | | (6x-8)(x+6)= | | 6s-6s=0 | | -9n+10=10+6n | | 5+7j+j=9j+1 | | 3.6-0.8a=-0.5a | | .4u+39.6=u | | 7x=12+35 | | p(x)=x^4-2x^3-13 | | 9x-2y=16 | | -3[6-(3n+2)]+16=4(6+n) | | 7(t-3)=2(t+9)+2t | | 8(y-5)+4y=-9(y+6) | | 4-4(b-4)=5(2b-3) | | 9w+2=4(w-2) | | y-6.7=1.7 | | 5m-2=(-m)-2 | | 2/15=11/12x | | 4n-5=5-2n | | 27=3y+3x | | 1(4x+6)=1(9x-24) |